2015
DOI: 10.1093/nar/gkv731
|View full text |Cite
|
Sign up to set email alerts
|

Novel insights into RNP granules by employing the trypanosome's microtubule skeleton as a molecular sieve

Abstract: RNP granules are ribonucleoprotein assemblies that regulate the post-transcriptional fate of mRNAs in all eukaryotes. Their exact function remains poorly understood, one reason for this is that RNP granule purification has not yet been achieved. We have exploited a unique feature of trypanosomes to prepare a cellular fraction highly enriched in starvation stress granules. First, granules remain trapped within the cage-like, subpellicular microtubule array of the trypanosome cytoskeleton while soluble proteins … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
144
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 80 publications
(161 citation statements)
references
References 90 publications
16
144
0
1
Order By: Relevance
“…PRO , but not TbPRMT1 ENZ , is reportedly phosphorylated (8,45), bound to mRNA (46), and trafficked to stress granules in starved trypanosomes (47). This suggests that TbPRMT1 PRO could be, in certain situations, operating independently of TbPRMT1 ENZ , possibly as a homodimer (Fig.…”
Section: Discussionmentioning
confidence: 94%
“…PRO , but not TbPRMT1 ENZ , is reportedly phosphorylated (8,45), bound to mRNA (46), and trafficked to stress granules in starved trypanosomes (47). This suggests that TbPRMT1 PRO could be, in certain situations, operating independently of TbPRMT1 ENZ , possibly as a homodimer (Fig.…”
Section: Discussionmentioning
confidence: 94%
“…Co-staining of the cells with AMCA which stains the cell surface and flagellar pocket demonstrated that the REG9.1 signal was only partly overlapping with the flagellar pocket (Fig 9B) and ‘no first antibody’ controls confirmed the signal was not caused by secondary antibody recognition of host antibodies in the flagellar pocket. Since REG9.1 has been detected in procyclic form stress granules by proteomic analysis [34], we explored whether REG9.1 coalesced from its uniform cytoplasmic distribution in procyclic forms to discrete foci upon starvation or heat shock. Under starvation conditions (2h in PBS) REG9.1 co-localised partially with the stress granule marker Scd6 [35] (S5A Fig), but this was not evident with heat shock, where Scd6 signal was also not obvious.…”
Section: Resultsmentioning
confidence: 99%
“…Lysis of trypanosomes in the presence of 1% Triton X-100 results in trapping of structures with a diameter of more than 24nm within the microtubule corset [21]. (For comparison, a ribosome is just under 30nm across.)…”
Section: Resultsmentioning
confidence: 99%
“…Some mRNAs that were excluded (<20%) from heat shock granules were also similarly absent from starvation granules [21]. Presumably these encode products that are required to recover from both starvation and heat shock.…”
Section: Discussionmentioning
confidence: 99%